Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1021/ac020538i
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantitation of Aprepitant Drug Substance Polymorphs by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy

Abstract: In this study, we report the use of attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FT-IR) for the identification and quantitation of two polymorphs of Aprepitant, a substance P antagonist for chemotherapy-induced emesis. Mixtures of the polymorph pair were prepared by weight and ATR-FT-IR spectra of the powdered samples were obtained over the wavelength range of 700-1500 cm(-1). Significant spectral differences between the two polymorphs at 1140 cm(-1) show that ATR-FT-IR can provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…Since MH is a readily soluble drug compound, the existence of polymorphism has no relevance to its typical clinical use as water-dissolved active substance. The present study confirms the potential of ATR FT-IR as a quick, easy and cheaper alternative to XRPD [24]; the technique is ideally suited for polymorph analysis, because it is precise, accurate and requires minimal sample preparation.…”
Section: Discussionsupporting
confidence: 82%
“…Since MH is a readily soluble drug compound, the existence of polymorphism has no relevance to its typical clinical use as water-dissolved active substance. The present study confirms the potential of ATR FT-IR as a quick, easy and cheaper alternative to XRPD [24]; the technique is ideally suited for polymorph analysis, because it is precise, accurate and requires minimal sample preparation.…”
Section: Discussionsupporting
confidence: 82%
“…Helmy et al 34 identified ATR-FTIR as a quantification technique by successfully calculating the contents of aprepitant polymorphs within mixtures. In the present case, the data in Figures 5a and 5b demonstrated the ability of ATR-FTIR to differentiate between the amorphous and crystalline salbutamol sulfate; in particular, the peaks in the wavelength range of 1500 to 900 cm −1 had been shown to be especially sensitive to differences in crystallinity.…”
Section: Quantification By Atr-ftirmentioning
confidence: 99%
“…PLS model with proper number of dimensions was derived and the model was validated using external test set. Detailed explanation of calibration routines applied in this context is described in [12].…”
Section: Mathematical Methods Applied For Spectral Datamentioning
confidence: 99%
“…Additional technique is beneficial to confirm the estimation derived from XRPD measurements. Vibration spectroscopic techniques such as diffuse reflectance (DRIFT) and attenuated total reflection (ATR) in the mid-FTIR bandwidth as well as NIR have previously been applied in polymorph characterizations [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%